Penguasaan Aritmatika Sosial Ditinjau Dari Pola Asuh Orang Tua Pada Siswa Kelas VII SMP Tahun Pelajaran 2021/2022 - Saniati Rofiqoh; Heru Kurniawan; Nila Kurniasih (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
This study aims to find out how the mastery of social arithmetic in terms of parenting style. This type of research is descriptive qualitative research. The research subjects were parents and students of class VII SMP Negeri 3 Wadaslintang with different parenting patterns, and 2 students and parents with authoritarian parenting patterns were selected, 2 students and parents with permissive parenting patterns and 2 students and parents with democratic parenting. Data collection methods used are questionnaires, interviews, tests, and documentation. Data analysis techniques were carried out by (1) data reduction (2) data presentation (3) verification. The results of the research show that students with permissive parenting styles experience (1) difficulty in understanding the questions (2) making a solution plan (3) implementing the solution plan, so that the social arithmetic mastery of students with permissive parenting styles is in the low category. Students with authoritarian parenting styles experience difficulty in carrying out problem solving plans, so that the mastery of social arithmetic of students with authoritarian parenting styles is in the medium category. Students with democratic parenting styles can solve problems well, so that students with democratic parenting styles mastery of social arithmetic is in the high category.